Analisis Ketepatan Kode Diagnosis Pada Kasus Penyakit Infeksi Saluran Pernapasan di Rumah Sakit Umum Daerah Ajibarang - Syifani, Annisa Zahra; Fauzi, Harry; Marini, Budiana (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2024)
Coding is one of the activities of processing medical record data by providing codes with letters or numbers or a combination of letters and numbers that represent data components. Coding is the activity of providing codes for the main diagnosis and secondary diagnosis in accordance with the 2010 version of ICD-10 published by WHO and providing action and procedure codes in accordance with the 2010 version of ICD-9-CM. Accuracy in coding disease diagnoses and actions is something that must be considered by medical recorders. The accuracy of coded data is crucial for medical recorders. The purpose of this research was to ascertain the level of coding accuracy in cases of respiratory tract infections at Ajibarang Hospital. The research was conducted using the descriptive quantitative analysis method with a sample of 90 medical records of patients with respiratory tract infections in August–October 2023 at RSUD Ajibarang. The conclusion of this research showed that of the 90 medical records of respiratory tract infection cases at Ajibarang Regional Hospital in August–October 2023 studied, there were 19 medical records with inappropriate codes (21.11%) and 71 medical records with appropriate codes (78.89%), which were identified as inaccurate factors using 5M (man, money, material, method, and machine).